Outcomes in patients with chronic lymphocytic leukemia and TP53 aberration who received first-line ibrutinib: a nationwide registry study from the Italian Medicines Agency - Gian Matteo Rigolin; Pier Paolo Olimpieri; Valentina Summa; Simone Celant; Lydia Scarfò; Lucia Tognolo; Maria Pia Ballardini; Antonio Urso; Mariarosaria Sessa; Silvia Gambara; Francesca Cura; Monica Fortini; et al. (Blood Cancer Journal, 2023)
Abstract In this analysis we describe the effectiveness of first-line ibrutinib in 747 patients with chronic lymphocytic leukemia (CLL) and TP53 aberrations in a nationwide study with a 100% capture of patients who received the study drug. Median age was 71 years (range 32–95). An estimated treatment persistence rate of 63.4% (95% CI 60.0%-67.0%) and survival rate of 82.6% (95% CI 79.9–85.4%) were recorded at 24 months. Disease progression or death were the reasons for discontinuation in 182/397 patients (45.8%). A higher risk of treatment discontinuation was found to be associated with age, ECOG-PS and pre-existing heart disease, whereas ECOG ≥ 1, age ≥ 70 years and male sex were associated with an increased risk of death. Median post-progression overall survival (OS) was 12.2 months (95% CI 9.2–22.0). Post-discontinuation median OS in patients who discontinued ibrutinib for other reasons was not reached (95% CI 42.3 months – NA). Ibrutinib was an effective first-line treatment for CLL and TP53 aberrations in patients treated at large academic centers and community practice hospitals. Clinical characteristics at baseline may influence the effectiveness of ibrutinib, whereas the experience of prescribing centers and multi-hit or single-hit TP53 aberrations had no impact on outcome in this high-risk population.